Analisis Optimalisasi Produksi dengan Linear Programming Melalui Metode Simpleks - Teguh Sriwidadi; Erni Agustina (Bina Nusantara University, 2013)
PD Utama Jaya Plasindo is a trading company which processes plastic resin. In the daily process, the company has many problems or constraints in production planning. Uncertainty demand of goods fluctuation has effect on shortage or surplus production. Other problems are raw materials, machine work hour, labour work hour, and the demand of the products. Simplex Method of Linear Programming purposes to maximize profit in linear function, Profit = 37 A + 46 B + 38 C + 46 D and linear functions of the seven constraints, Raw materials = 7 A + 5,8 B + 8,6 C + 7,6 D ≤ 180.000 grams, Machine Work Hour = 2,5 A + 3 B + 2 C + 2,5 D ≤86.400 seconds, Labor Work Hour = 5 A + 5 B + 5 C + 5 D ≤ 115.200 seconds, Demands of GRX 25 = A ≤2400 pcs, demand of GTW 25 = B ≤ 7200 pcs, demand of GTX 25 = C ≤ 3000 pcs, and demand of GTX 25 M = D ≤ 6600 pcs. The total profit earned by PD Utama Jaya Plasindo from plastic buckle products is Rp 837,000.00 per day and for 20 efective days is Rp 16,752,000.00 with the assumption of profit is in accordance with fixed objective and constraint functions.